Decentralization and Distribution Primary Education Access in Indonesia 2014 - Benita, Novinaz (Jurnal Ilmiah Administrasi Publik, 2016)
This paper examines decentralisation and distribution of access to primary school in Indonesia. Data come from Indonesia National Socio Economic Survey 2014, and statistic reports from Ministry of education, Ministry Of Finance, and General Election Commision. Descriptive statistic is used to describe spatial distribution of decentralization in primary education system and distribution of primary education access. The results show there are districts disparities in decentralization of primary education system and primary education access especially between district within Java islands and Papua islands. The results highlight the need to improving decentralization performance to achieve universal primary education in Indonesia, particularly within districts outside Java islands. Improving bureaucracy capacity particularly teachers is important to improve decentralization performance in primary school access.